STUDY CONSUMER RECEPTION OF NORI SEAWEED (Echeuma cottonii) WITH THE ADDITION PROTEIN CONCENTRATE OF FISH GABUS (Channa striata) - Zela Arniyanti; Sukirno Sukirno; Suparmi Suparmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRAK This study aims to determine consumer acceptance of nori seaweed that has been added fish protein concentrate cork (KPI) with the different treatments. The design used was Completely Randomized Design (RAL) with nori without addition of KPI (N0) , nori addition of 5% KPI (N1), and nori addition of 10% KPI (N2) treatment. The parameters tested were consist of organoleptic and proximate test. Proximate test including moisture content, ash content, protein content, and crude fiber content.The results showed that (N1) treatment with 5% addition of KPI was the best treatment for organoleptic test and (N2) treatment with 10% addition of KPI for proximate test with 93.75% color rating, 81.25% odor, 91.25% texture, 76.25% 10.05%, ash content 5.43%, protein content 30.07%, and crude fiber content 31.30%. Keywords :gabus fish, organoleptic, proximate, protein, seaweed.